Assessment of Arterial Distensibility by Automatic Pulse Wave Velocity Measurement: Validation and Clinical Application Studies - Asmar, Roland; Benetos, Athanase; Topouchian, Jirar; Laurent, Pierre; Pannier, Bruno; Brisac, Anne-Marie; Target, Ralph; Levy, Bernard I. (Hypertension (Dallas, Tex. 1979), 1995)
Pulse wave velocity is widely used as an index of arterial distensibility. The aim of this study was to evaluate the accuracy of a new automatic device to measure it and then to analyze the major determinants of pulse wave velocity by application of this device in a large population. We evaluated the accuracy of on-line and computerized measurement of pulse wave velocity using an algorithm based on the time-shifted and repeated linear correlation calculation between the initial rise in pressure waveforms compared with the reference method (manual calculation) in 56 subjects. The results, analyzed according to the recommendations of Bland and Altman, showed a mean difference of -0.20 plus/minus 0.45 m/s for the mean carotid-femoral pulse wave velocity values (reference method, 11.05 plus/minus 2.58 m/s; automatic device, 10.85 plus/minus 2.44 m/s). The inter-reproducibility and intrareproducibility of measurements by each method were analyzed with the use of the repeatability coefficient according to the British Standards Institution. The interobserver repeatability coefficient was 0.947 for the manual method and 0.890 for the automatic, and intraobserver repeatability coefficients were 0.938 and 0.935, respectively. We evaluated the major determinants of the carotid-femoral pulse wave velocity measured by the automatic method in a separate study performed in 418 subjects of both sexes without any cardiovascular treatment or complication (18 to 77 years of age; 98 to 222 mm Hg systolic and 62 to 130 mm Hg diastolic pressure). Multiple regression analysis between pulse wave velocity and clinical parameters (age, sex, weight, height, smoking, arterial blood pressure, heart rate) and biological plasma parameters (total cholesterol, high-density lipoprotein cholesterol, glycemia) showed that pulse wave velocity correlated positively and independently with age and systolic pressure (r = .47; P < .001) according to the Equation PulseWave Velocity = 0.07 Systolic Pressure (mm Hg) + 0.09 Age (y)-4.3 (m/s). Similar results were obtained in the normotensive and hypertensive subgroups when analyzed separately. Pulse wave velocity can be easily and automatically determined. Its measurement is accurate and highly reproducible, and its major determinants are well established. It is of great interest to evaluate in large populations the therapeutic and epidemiological applications of an arterial parameter as evaluated by aortic pulse wave velocity. (Hypertension. 1995;26:485-490.)